Analisis Keputusan Pembelian di Marketplace - Ulul Azmi; Efriyani Sumastuti; Bayu Kurniawan (Yayasan Literasi Sains Indonesia, 2023)
This study aims to explain the ANALYSIS OF PURCHASING DECISIONS IN THE MARKETPLACE (Case Study on Students of the Management Study Program, Faculty of Economics and Business, PGRI Semarang University). This type of research is quantitative. The population in this study were students of the Management Study Program, Faculty of Economics and Business, PGRI Semarang University. Data collection used questionnaire result sheets that were distributed to 307 respondents but which filled in 307 respondents. Data collection techniques in this study used primer data and questionnaires with Multiple Linear Regression Analysis, with the help of SPSS software. The results of this study show that for the t test there is a positive and significant influence on the product review variable (X1) on the marketplace purchase decision, there is a positive and significant influence on the promotion variable (X2) on the marketplace purchase decision, There is a positive and significant influence on the price variable (X3) on marketplace purchasing decisions, there is a positive and significant influence on the brand image variable (X4) on marketplace purchasing decisions and there is a positive and significant influence on the product quality variable (X5) on marketplace purchasing decisions.